2016
DOI: 10.1007/s10531-016-1117-7
|View full text |Cite
|
Sign up to set email alerts
|

A poor international standard for trap selectivity threatens carnivore conservation

Abstract: Unintentional mortality of endangered carnivores due to non-selective trapping is important for conservation and warrants urgent attention. Currently, non-selective traps are being approved and used based on trap selectivity tests conducted according to International Organization for Standardization (ISO) guidelines. We review these guidelines and find them inadequate, because: 1) the ISO definition of selectivity does not account for relative abundance of target and non-target species and does not therefore m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Over the last 20 years, countless datasets have been collected on the impact of trapping on animal welfare [ 10 ], trap selectivity and the impact of trapping on the persistence of animal populations [ 13 , 15 ], and the ethics of wildlife professionals and managers with respect to mammal trapping [ 2 , 9 , 10 , 72 , 97 ]. The development of better trapping standards should not require another 20 years due to a lack of definitions, a poor understanding of trapping research and development technology, or conceptual views about human–wildlife relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last 20 years, countless datasets have been collected on the impact of trapping on animal welfare [ 10 ], trap selectivity and the impact of trapping on the persistence of animal populations [ 13 , 15 ], and the ethics of wildlife professionals and managers with respect to mammal trapping [ 2 , 9 , 10 , 72 , 97 ]. The development of better trapping standards should not require another 20 years due to a lack of definitions, a poor understanding of trapping research and development technology, or conceptual views about human–wildlife relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The stated principle is to evaluate, in the field, the capability of a trap to capture target rather than non-target animals by recording the number of each that is captured by the test trap and by a control trap [ 6 , 7 ]. Virgós et al [ 13 ] reviewed these guidelines and found them inadequate because (1) the ISO definition of selectivity does not account for the relative abundance of target and non-target species and does not therefore meaningfully reflect selectivity; (2) the guidelines’ methodology at best quantifies the relative selectivity of one trap against another, which is of limited use unless the control trap is known to have an acceptable level of absolute selectivity for the target species; (3) as with capture efficiency, information on relative trap selectivity cannot simply be extrapolated elsewhere, unless species assemblage and relative species abundances are consistent. The ISO definition of trap selectivity in effect provides only a simple capture proportion and therefore does not represent trap selectivity [ 13 ].…”
Section: Hypothesis 7: the Aihts Criteria To Assess Trap Efficiencmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, the continued and increasing rate of incidental capture of animals that commonly include the most severely threatened species (Corlett ; Virgós et al. ) may jeopardize their permanence in the wild (Dulvy et al. ; Brashares et al.…”
Section: Conservation Challenges In the Developing Worldmentioning
confidence: 99%
“…Incidental capture of aquatic animals as bycatch in fisheries accounts for 40% of the global harvest (Keledjian et al 2014), and on land, unintentional captures of mammals and birds also occur via unselective capture methods (Noss 1998;Zöckler et al 2010;Becker et al 2013). Globally, the continued and increasing rate of incidental capture of animals that commonly include the most severely threatened species (Corlett 2007;Virgós et al 2016) may jeopardize their permanence in the wild (Dulvy et al 2003;Brashares et al 2004;Hays et al 2004). Remediation of this problem has chiefly focused on reducing the probability of capturing threatened species (Albrechtsen et al 2007;Komoroske & Lewison 2015;Leeney et al 2015).…”
Section: Conservation Challenges In the Developing Worldmentioning
confidence: 99%